Antibioticograms of Vibrio cholerae non-O1/non-O139 Strains Isolated from Humans within 1968-2009 - N. A. Selyanskaya; I. V. Ryzhko; L. M. Verkina; A. V. Trishina; A. V. Mironova; M. V. Akulova (Антибиотики и Химиотерапия)
Analysis of the antibioticograms of the Vibrio cholerae non-O1/non-O139 strains showed that in the cultures isolated in the Rostov Region in 1968-1975 there were present markers of resistance to ampicillin (7%), kanamycin (15.8%), rifampicin (3.5%) and trimetoprim/sulfamethoxazole (14%). Among the strains isolated in the Ukraine in 1975 14% was resistant to ampicillin. More than a half of the strains isolated in Uzbekistan in 1990 and 2000-2001, in the Arkhangelsk Region in 1999-2000 and in the Kalmykia in 1999-2005 was antibiotic resistant. In the above regions the strains were resistant to ampicillin (12.5-44.4%), kanamycin (11-55%), rifampicin (1.9-12.5%) and trimetoprim/sulfamethoxazole (25-62.5%). Among the cultures isolated in Uzbekistan in 1990 and 2000-2001 25 and 7.8% were resistant to furazolidone and 31.25% was resistant to streptomycin (1990). All the cultures isolated in the Rostov Region in 2005-2009 were resistant to ampicillin, 50% was resistant to ceftazidim, 57% was resistant to streptomycin and furazolidone, 7.2% was resistant to kanamycin and 14% was resistant to trimetoprim/sulfamethoxazole. The studies revealed an increase of the extent of the V.cholerae non-O1/non-O139 resistance spectrum within 1968-2009, simultaneous presence of up to 5 diverse resistance markers and a variety of their combinations, that requires the use of antibacterials for the treatment of the diseases due to the vibrios in strict compliance with the pathogen antibioticogram and their early replace by more efficient drugs.